Functional fitness build your fittest body ever with Australia's body coach - Collins, Paul (The body coach series, 2009)
Presents practical, easy-to-follow exercises to condition your body for athletic and sports performance. This title - for men and women - provides step-by-step coaching advice and workouts utilizing body weight, fitness balls, medicine balls, plyometrics, resistance bands, stability and speed training equipment